1996
DOI: 10.1212/wnl.47.1.272
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel accumulation in humans with painful neuromas

Abstract: Painful neuromas from 16 patients were examined using site-specific antisodium channel antibodies employed in immunocytochemical and radioimmunoassay methods. Normal sural nerves from six of these patients served as controls. Immunocytochemistry showed abnormal segmental accumulation of sodium channels within many axons in the neuromas. Dens immunolocalization was especially apparent within the axonal tips. Radioimmunoassay confirmed a significantly greater density of sodium channels in the neuromas as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 5 publications
3
76
1
4
Order By: Relevance
“…The common sciatic nerves at the level of the CCI with or without NT-3 infusion were processed to detect either Na v 1.8 or Na v 1.9 protein. Consistent with previous reports (Devor et al, 1989;England et al, 1994England et al, , 1996Amir et al, 1999), both Na v 1.8 and Na v 1.9 protein levels were more highly localized to the constriction sites 7 days following CCI (CCI; Figure 7 bottom). Infusion of NT-3 attenuated this redistribution as evidenced by a reduction in relative levels of Na v 1.8 and Na v 1.9 protein at the constriction sites of the CCI + NT-3 treated nerves (Figure 7 bottom).…”
Section: Nt-3 Significantly Attenuates Neuronal Na V 18 Mrna Expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…The common sciatic nerves at the level of the CCI with or without NT-3 infusion were processed to detect either Na v 1.8 or Na v 1.9 protein. Consistent with previous reports (Devor et al, 1989;England et al, 1994England et al, , 1996Amir et al, 1999), both Na v 1.8 and Na v 1.9 protein levels were more highly localized to the constriction sites 7 days following CCI (CCI; Figure 7 bottom). Infusion of NT-3 attenuated this redistribution as evidenced by a reduction in relative levels of Na v 1.8 and Na v 1.9 protein at the constriction sites of the CCI + NT-3 treated nerves (Figure 7 bottom).…”
Section: Nt-3 Significantly Attenuates Neuronal Na V 18 Mrna Expressionsupporting
confidence: 91%
“…Interestingly, it appears that Na v 1.9 does play a role in hypersensitivity produced by the application of inflammatory mediators to the peripheral terminals of the nociceptors (Amaya et al, 2006). It has been proposed that Na v 1.9 plays a crucial role in setting the resting membrane potential of a neuron and that an increased density of this channel, such as is seen with the accumulation of voltage gated sodium channels at the tips of the injured neurons (Devor et al, 1989;England et al, 1994England et al, , 1996, may hyperpolarize the neuron (Herzog et al, 2001). It thus appears that the decreased expression of Na v 1.8 by exogenous NT-3 likely plays an important role in preventing the development of thermal hyperalgesia, while the decreased expression of Na v 1.9 may prevent hyperexcitablity and/or repetitive firing of the neuron by increasing the resting membrane potential of these neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies using immunocytochemical methods have demonstrated increased numbers of sodium channels within the distal parts of injured axons. [12][13][14] Contemporary molecular techniques have recently allowed us to examine the molecular basis for these changes and to ask whether different types of sodium channels are deployed within neurons following injury ( Figure 2). We have thus learned that there is an upregulation of several sodium channel genes, including the previously silent ␣-III sodium channel gene 15 and a down-regulation of other sodium channel genes, including ␣-SNS and NaN in DRG neurons following axonal transection (Figure 2).…”
Section: Sodium Channel Expression Is Dynamic: I Developing and Injumentioning
confidence: 99%